2022
DOI: 10.21203/rs.3.rs-2222674/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation between immune-related adverse events and long-terms outcome in pembrolizumab-treated patients with unresectable hepatocellular carcinoma: a retrospective study

Abstract: Background Although immune checkpoint inhibitors (ICIs) therapy has improved the prognosis of unresectable hepatocellular carcinoma (HCC), it has also resulted in the unique immune-related adverse events (irAE). The relationship between irAE and treatment outcomes in ICIs-treated advanced HCC patients remains unknown. Methods From March 2019 to February 2021, a total of 190 unresectable HCC (BCLC C) patients receiving Pembrolizumab treatment were retrospectively reviewed. Overall survival (OS) was the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Immune tolerance imbalance and inflammatory side effects caused by ICIs are known as irAEs [114].The mechanism of irAEs is not well understood and may be related to the enhancement of systemic T cell activity by ICIs, which in turn leads to the loss of immune tolerance in individual organs [115]. Several studies [116][117][118] have shown that the occurrence of irAEs is associated with clinical benefit in HCC patients treated with ICIs and may be a potential biomarker for predicting clinical outcomes of ICI therapy in HCC patients. Xu et al [116] found that among 65 HCC patients receiving anti-PD-1 antibodies, the median PFS (302 days vs. 148 days, p = 0.004) and median OS (374 days vs. 279 days, p = 0.038) were better in the irAE group than in the non-irAE group.…”
Section: Immune-related Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune tolerance imbalance and inflammatory side effects caused by ICIs are known as irAEs [114].The mechanism of irAEs is not well understood and may be related to the enhancement of systemic T cell activity by ICIs, which in turn leads to the loss of immune tolerance in individual organs [115]. Several studies [116][117][118] have shown that the occurrence of irAEs is associated with clinical benefit in HCC patients treated with ICIs and may be a potential biomarker for predicting clinical outcomes of ICI therapy in HCC patients. Xu et al [116] found that among 65 HCC patients receiving anti-PD-1 antibodies, the median PFS (302 days vs. 148 days, p = 0.004) and median OS (374 days vs. 279 days, p = 0.038) were better in the irAE group than in the non-irAE group.…”
Section: Immune-related Adverse Eventsmentioning
confidence: 99%
“…And people who discontinued due to adverse reactions had significantly longer median OS than people who did not discontinue due to adverse reactions (not reached vs. 11.2 months, p = 0.001) [117]. In a retrospective study of 190 patients with unresectable HCC treated with pembrolizumab by Zhou et al [118], OS [517 d (95% CI: 423-562) vs. 431 d (95% CI: 412-485), p = 0.011] and time to progression [125 d (95% CI: 89-154) vs. 87 d (95% CI: 61-98), p = 0.004] were significantly longer in hypothyroid patients than in those without irAEs. In addition to the type of irAEs, the prognosis of HCC patients treated with ICIs may be related to the severity of irAEs.…”
Section: Immune-related Adverse Eventsmentioning
confidence: 99%